Scar Tissue‐Targeting Polymer Micelle for Spinal Cord Injury Treatment. Issue 8 (31st January 2020) - Wang, Jingkai; Li, Dongdong; Liang, Chengzhen; Wang, Chenggui; Zhou, Xiaopeng; Ying, Liwei; Tao, Yiqing; Xu, Hongxia; Shu, Jiawei; Huang, Xianpeng; Gong, Zhe; Xia, Kaishun; et al.
Abstract: Spinal cord injury (SCI) is a devastating disorder, leading to permanent motor and sensory deficit. Despite recent advances in neurosciences, the treatment efficacy on SCI patients remains unsatisfactory, mainly due to the poor accumulation, short retention, and lack of controlled release of therapeutics in lesion tissue. Herein, an injured spinal cord targeting prodrug polymer micelle is built. An esterase‐responsive bond is used to link apocynin (APO) monomer, because of the enhanced esterase activity found in microglia cells after activation, which ensures a controlled degradation of APO prodrug (Allyloxypolyethyleneglycol‐ b ‐poly [2‐(((4‐acetyl‐2‐methoxyphenoxy)carbonyl)oxy)ethyl methacrylate], APEG‐PAPO or PAPO) by activated microglia cells. A scar tissue‐homing peptide (cysteine‐alanine‐glutamine‐lysine, CAQK) is introduced to the PAPO to endow the polymer micelle the lesion tissue‐targeting ability. As a result, this CAQK‐modified prodrug micelle (cPAM) exhibits an improved accumulation and prolonged retention in lesion tissue compared to the control micelle. The cPAM also leads to superior tissue protection and sustained motor function recovery than the control groups in a mouse model of SCI. In conclusion, the cPAM induces an effective treatment of SCI by the lesion tissue specific delivery of the prodrug polymer via its robust scar binding effect, making the scar tissue a drug releasing platform for sustained treatment of SCI. Abstract : An injured spinal‐cord‐targeting prodrug polymer micelle is built with a scar tissue‐homing peptide and the esterase‐responsive apocynin‐based polymer. The micelle actively accumulates in the lesion center after i.v. injection, binding to chondroitin sulfate proteoglycan, and can be degraded by activated microglia, sequentially reducing ROS production and leading to a promoted motor function recovery.